THE CARD SORT TYPE ACTIVE LEARNING METHOD ON CREATIVE THINKING ABILITY IN CLASS V SOCIAL SCIENCES LEARNING SDN MARGA JAYA I BEKASI CITY - Pratiwi, Nur Azizah; Putri, Fara Diba Catur (PROGRES PENDIDIKAN, 2024)
This study aims to determine the effect of using the card sort type of active learning method on the ability to think creatively in class V social studies students at SDN Marga Jaya I, Bekasi City. This study uses a quantitative approach, with the subject being Class V teachers and fifth grade students at SDN Marga Jaya I, Bekasi City. The research sample consisted of two classes, namely the experimental class and the control class. In the experimental class there were 27 students, and in the control class there were 26 students. In obtaining the data, the researcher used the Social Sciences Creative Thinking Ability test method for elementary school students in the form of essay choice questions, observation, and documentation. The data analysis technique used is inferential analysis by testing the hypothesis using the t-test statistic, a significant level of 5% = 0.05. Inferential analysis is an analytical technique that can be used to determine whether the hypothesis in the study is accepted or rejected. Based on the results of the study, it can be concluded that the use of the card sort type of active learning method on the ability to think creatively in class V social studies students at SDN Marga Jaya I, Bekasi City. This is shown in the results of the average value of the experimental class after being given the card sort learning treatment, which is 67.11, and the control class which is given the conventional learning treatment is 61.92.